Giant Breast Hypertrophy in Juvenile: A Rare Case - Dila Junita; Edmond Rukmana Wikanta (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Juvenile hypertrophy of the breast (JHB) is a benign condition that can lead to gigantomastia in adolescence. The development of breast enlargement in adolescence can cause both physical and psychosocial problems. Therefore, appropriate investigation and proper management at an early stage of the disease are very important. One of the treatment modalities is breast reduction surgery which ideal and offers an improvement in the quality of life. Case Presentation: A 13-year-old female with massive bilateral breast enlargement for a period of 8 months. The patient also complained of severe back pain and neck discomfort since her breast progressively enlarged. Psychosocial problems were recorded. Right breast reduction was performed and closed with inverted-T mammoplasty. The post-operative period was uneventful, and the patient was discharged on day 5 after the operation. Conclusions: Reduction mammoplasty is well accepted by adolescents with juvenile breast hypertrophy and can improve physical and psychological outcomes.